2021
DOI: 10.1186/s13071-020-04507-2
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis control in Ghana (1974–2016)

Abstract: Background The control of onchocerciasis in Ghana started in 1974 under the auspices of the Onchocerciasis Control Programme (OCP). Between 1974 and 2002, a combination of approaches including vector control, mobile community ivermectin treatment, and community-directed treatment with ivermectin (CDTI) were employed. From 1997, CDTI became the main control strategy employed by the Ghana OCP (GOCP). This review was undertaken to assess the impact of the control interventions on onchocerciasis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…Despite more than 40 years of concerted control efforts leading to signi cant reduction in onchocerciasis MF prevalence, the disease which has potentially severe impacts on the eyes and skin still remains endemic in some districts in Ghana as reported recently by Biritwum et al, [10]. This present study is the rst in determining the impact of MDA on the prevalence of onchocerciasis and its associated clinical manifestations in Sefwi Akontombra, a mesoendemic district in Ghana.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Despite more than 40 years of concerted control efforts leading to signi cant reduction in onchocerciasis MF prevalence, the disease which has potentially severe impacts on the eyes and skin still remains endemic in some districts in Ghana as reported recently by Biritwum et al, [10]. This present study is the rst in determining the impact of MDA on the prevalence of onchocerciasis and its associated clinical manifestations in Sefwi Akontombra, a mesoendemic district in Ghana.…”
Section: Discussionmentioning
confidence: 66%
“…100 million IVM tablets distributed between 1997 and 2016. The review also revealed that the nodule and MF prevalence in the Western Region as at 2008 was 2.89% and 3.57% respectively [10].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Villages were selected on the criteria that (a) there was evidence of exposure to S. damnosum s. l. vector bites [30,42], (b) they were under current ivermectin treatment as part of the national onchocerciasis control programme [43], (c) the villages comprised >200 residents, and (d) the villages represented variable ABRs based on previous records [30,42]. Five villages were selected; due to the proximity of two of the villages, these were grouped into a single cluster (Asubende and Senyase (ASU/SEN) resulting in four village clusters.…”
Section: Recruitment Blood Sampling and Demographic Informationmentioning
confidence: 99%